Pengaruh Sumber Pembelajaran Lingkungan Sekitar dalam Pembelajaran Membaca Siswa Kelas 2 SD Inpres Bontomarinra - Fitrahwati, Fitrahwati; Ramly, Ramly; Hasriani, Hasriani (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the effect of neighbourhood learning resources in learning to read. This research is included in quantitative research with the type of pre-experiment. The population in this study were Grade 2 students of SD Inpres Bontomarinra totalling 72 students. The sample in this study amounted to 16 students. The data collection technique in this study was in the form of a test. The collected data were analysed with descriptive statistics and inferential statistics.  The results showed that the application of environmental learning resources had an effect on the reading learning outcomes of Grade 2 students of SD Inpres Bontomarinra The description of the conclusion is as follows. The learning outcomes of recognising alphabetic letters before using environmental materials around Class 2 SD Inpres Bontomarinra students are categorised as less capable with an average score of 13.75. Learning outcomes of recognising alphabetic letters after using environmental materials around Class 2 SD Inpres Bontomarinra students are categorised as capable with an average score of 22.94.